Leadership as a Catalyst for Nigeria’s National Development: A Behavioral and Systems Perspective - Dembele, Mary (Journal of Law & Policy Review, 2025)
This paper examines the role of leadership as a catalyst for Nigeria's national development from a behavioural and systems perspective. The study employs a qualitative, conceptual review Design, based on a systematic analysis of peer-reviewed literature, policy documents, and theoretical models related to leadership, governance, and development. Drawing on behavioural leadership theory, systems management theory, and the leadership grid framework, the study analyses how leadership practices shape institutional effectiveness and developmental outcomes in Nigeria. The findings indicate that deficiencies in leadership orientation, ethical standards, emotional intelligence, coordination capacity, and institutional accountability constitute significant barriers to Nigeria’s development performance. The analysis further shows that leadership practices that balance task orientation with people-centred engagement, particularly those aligned with the 9,9 leadership grid, are more likely to enhance transparency, innovation, institutional trust, and sustainable growth. The study also finds that the weak integration of leadership development into national planning frameworks limits Nigeria’s capacity to translate policy goals, including the Sustainable Development Goals, into tangible outcomes. The paper contributes to leadership and development scholarship by offering an integrated behavioural–systems framework for understanding leadership failure and reform in Nigeria. It recommends embedding leadership development into national development planning and establishing a dedicated Nigerian Institute for Leadership to enhance capacity, uphold ethical standards, and foster long-term governance effectiveness.